Design, development, and performance evaluation of a power-operated jute fiber extraction machine - Karim, Md. Rejaul; Hoque, Muhammad Arshadul; Chawdhury, Alamgir; Faruk-Ul-Islam; Ahmed, Sharif; EL Sabagh, Ayman; Hossain, Akbar (MDPI, 2021)
Jute is the golden fiber of Bangladesh, but its production is declining due to the involvement of higher production and processing costs, where a major portion of the cost is needed for fiber extraction. Labor unavailability and increasing labor cost have led to higher jute fiber production cost. To address these issues, this study looks at the development of a power-operated and cost-effective fiber extraction machine aiming at reducing the production cost. The study was conducted at the Rangpur regional office premises of Practical Action in Bangladesh, and the developed machine was branded as “Aashkol”, which had the following major parts: a feeding tray, a primary extraction roller, a secondary extraction roller, grabbing rollers, fiber collection stand, base frame, protection cover, and a spring-loaded tray under the primary extraction roller. The Aashkol can extract green ribbon from the jute stem, but jute sticks were broken down into smaller pieces (3–6 cm). The performance evaluation of the machine was conducted using different types of jute (Deshi, Kenaf, and Tossa) and compared with another jute extraction machine (KP model, introduced by Karupannya Rangpur Ltd.). The Aashkol-based extraction and improved retting systems were also evaluated and compared with traditional jute extraction systems. The jute stem input capacity (4.99 t h−1) of the Aashkol was 47.6% higher than the KP model (3.38 t h−1). Compared with the traditional system, across jute types, the Aashkol produced a 9% higher fiber yield and saved 46% retting time. Overall, the Aashkol reduced 90% of the labor requirement and saved 11.6 USD t−1 in jute fiber extraction and retting than the traditional method.